A Study On Gen Z’s Perception Towards Buy Now Pay Later (BNPL) Schemes in Ahmedabad City. - Kavya Patel; Ritu Sharma; Jignesh Vidani (Journal of Advanced Research in Economics and Business Management, 2025)
This study investigates the awareness, perception, and usage patterns of Buy Now Pay Later (BNPL) schemes among young adults in India, focusing on their financial behavior, behaviour,social influences, and risk perceptions. A sample of 150 respondents, primarily aged 18–26 years, was surveyed to examine demographic characteristics, adoption trends, and behavioral behaviour,behaviouralattitudes toward BNPL services offered by fintech companies. The findings reveal that a significant majority of participants are aware of BNPL schemes (66%) and perceive them as easy to use (64%) and flexible in managing expenses (52%). At the same time, concerns regarding impulsive buying (46%) and hidden charges or penalties (46%) were prevalent, highlighting the dual nature of BNPL as both a convenient financial tool and a potential source of financial risk. Peer influence emerged as an important factor, with 40% of respondents acknowledging the impact of friends, social media, and influencers on their decision to use BNPL. Furthermore, 50% of participants emphasizedbehaviouralemphasised the need for proper regulation and consumer protection, reinforcing the importance of transparency and ethical practices in fintech services. Reliability analysis confirmed the internal consistency of the survey instrument (Cronbach’s Alpha = 0.851), ensuring robust measurement of the constructs studied. The research offers valuable theoretical insights by linking technology adoption models, behaviouralemphasisedbehavioural economics, and social influence theories to BNPL usage among Gen Z. Practical implications suggest the need for fintech companies to design user-friendly, transparent, and socially endorsed credit products while implementing tools to encourage responsible financial behaviour.